Composite solid electrolyte membrane, preparation method thereof, solid-state battery and electric device

By adopting a composite solid electrolyte membrane in solid-state batteries, the membrane consists of mesh fiber material, solid electrolyte, lithium salt and molten salt, the shortcomings in solid-state battery solid electrolyte materials in ionic conductivity and mechanical properties are solved, and the cycle stability and durability of the battery are significantly improved.

CN119695252APending Publication Date: 2025-03-25ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411882075.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The solid electrolyte materials of existing solid-state batteries have shortcomings in terms of ionic conductivity and mechanical properties, resulting in poor cycling stability and durability of the batteries.

Method used

A composite solid electrolyte membrane is used, which consists of a mesh fiber material, a solid electrolyte, a lithium salt and a molten salt. The molten salt is selected as tetrabutyl ammonium bistrifluoromethanesulfonate. The electrolyte composition is uniformly attached to the mesh and its surface of the mesh of the mesh fiber material through pulping and drying processes.

Benefits of technology

It significantly improves the ion conductivity and mechanical strength of the solid electrolyte membrane, improves the cycle stability and durability of the solid-state battery, and thus improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198440130000101
    Figure BDA0005198440130000101
  • Figure BDA0005198440130000111
    Figure BDA0005198440130000111
Patent Text Reader

Abstract

The invention discloses a composite solid electrolyte membrane, a preparation method thereof, a solid-state battery and an electric device. The composite solid electrolyte membrane comprises the following components: a reticular fiber material; the electrolyte composition is completely attached into the meshes of the reticular fiber material, or is simultaneously attached into the meshes and at least one side surface of the reticular fiber material; the electrolyte composition comprises a solid electrolyte, a lithium salt and a molten salt, the molten salt is selected from tetrabutyl bis (trifluoromethanesulfonic acid) ammonium, and the mass ratio of the molten salt to the lithium salt is less than or equal to 1: 1. Through component matching, higher ionic conductivity and mechanical properties are obtained, the composite material can be used for preparing a solid-state lithium ion battery, and the cycling stability and the use safety are improved. The invention also provides a preparation method of the composite solid electrolyte membrane, a solid-state battery and an electric device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a composite solid-state electrolyte membrane, a preparation method thereof, a solid-state battery and an electrical device. Background Art

[0002] As the next generation of lithium battery technology, solid-state batteries inherit the advantages of traditional secondary batteries and have outstanding advantages in safety, energy density, etc. Compared with traditional liquid electrolyte systems, solid-state batteries use solid electrolytes, which can effectively improve battery safety. However, as a solid-phase material, the contact between solid electrolyte particles is relatively loose and the wettability is poor, which directly affects ionic conductivity.

[0003] At present, the commonly used method to improve the ionic conductivity of solid electrolytes is to use isostatic pressing technology, which promotes the contact and interface fusion between solid electrolyte particles by pressurizing. However, isostatic pressing treatment often fails to ensure the mechanical properties of the electrolyte membrane, and is prone to defects such as breakage and cracks. These defects will cause the ion conduction path to be cut off, directly affecting the overall performance of the battery. At the same time, the frequent changes in volume during the solid-solid battery cycle will aggravate the failure of solid-solid point contact, destroy the interface state, and cause capacity decay, resulting in unsatisfactory performance of the solid-state battery, or even inability to use it normally.

[0004] Therefore, there is still a need to develop a solid electrolyte material with higher ionic conductivity and mechanical strength. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a composite solid electrolyte membrane with higher ion conductivity and mechanical properties, which helps to improve the durability and cycle stability of solid-state batteries, thereby improving the overall performance of the battery.

[0006] The present invention also provides a method for preparing the composite solid electrolyte membrane.

[0007] The invention also provides a solid-state battery.

[0008] The invention also provides an electric device.

[0009] Specifically, the first aspect of the present invention relates to a composite solid electrolyte membrane, comprising the following components: a mesh fiber material; an electrolyte composition, wherein the electrolyte composition is entirely attached to the mesh holes of the mesh fiber material, or is simultaneously attached to the mesh holes and to at least one side surface of the mesh fiber material; the electrolyte composition comprises a solid electrolyte, a lithium salt and a molten salt, wherein the molten salt is selected from tetrabutylammonium bistrifluoromethanesulfonate, and the mass ratio of the molten salt to the lithium salt is less than or equal to 1:1.

[0010] The composite solid electrolyte membrane according to the first aspect of the present invention has at least the following beneficial effects:

[0011] By combining solid electrolytes, lithium salts, molten salts and mesh fiber materials, the unique advantages of each component are fully utilized to obtain a solid electrolyte membrane with high conductivity, high safety and high mechanical strength.

[0012] Solid electrolytes are used to provide stable ion conduction channels and chemical stability over a wide temperature range. Molten salts can be filled in the interface of solid electrolyte particles and the mesh of mesh fiber materials to further improve ion conductivity and interface strength. Compared with other molten salts, tetrabutylammonium bistrifluoromethanesulfonate (TBA-TFSA or TBA-TFSI, CAS No.: 210230-40-3) has a lower melting point and good affinity for solid electrolytes. It is easier to penetrate into the pores of the solid electrolyte membrane, improving ion conductivity. At the same time, TBA-TFSA has a low modulus, provides a buffering effect, and improves mechanical properties. In addition, TBA-TFSA has good chemical stability, can reduce side reactions, and improve stability. When used in combination with lithium salts, it helps to form a stable solid electrolyte interface layer (SEI) at the interface between the electrode and the electrolyte, optimize the ion transmission channel, reduce the interface impedance, and improve the interface stability.

[0013] By rationally optimizing the mass ratio of lithium salt to TBA-TFSA, it is helpful to give full play to the advantages of lithium salt in ionic conductivity. If the proportion of lithium salt is too low, it may not provide sufficient ion source, resulting in insufficient ionic conductivity.

[0014] On the one hand, the mesh fiber material can provide structural support and improve mechanical strength; on the other hand, it is conducive to building an ion conduction network and further improving ion conductivity.

[0015] Therefore, the present invention significantly improves the ionic conductivity and mechanical strength of the solid electrolyte membrane by rationally matching the solid electrolyte, TBA-TFSA, lithium salt and mesh fiber material, which helps to improve the cycle stability and durability of the solid-state battery.

[0016] According to some embodiments of the present invention, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide (Li-TFSA or Li-TFSI), lithium bis(fluorosulfonyl)imide, and lithium oxalate.

[0017] According to some embodiments of the present invention, the lithium salt is selected from Li-TFSA. Li-TFSA has high chemical stability and can form a more stable SEI film between the solid electrolyte and the electrode, thereby improving the safety of the battery.

[0018] According to some embodiments of the present invention, the mass ratio of the molten salt to the lithium salt is 0.01 to 0.5:1, and non-limiting examples include: 0.01:1, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1 or any value therebetween. A lower ratio of molten salt can reduce its adverse effect on ionic conductivity, give full play to the advantages of lithium salt in ionic conductivity, and facilitate the formation of a more stable SEI film.

[0019] According to some embodiments of the present invention, the mass ratio of the molten salt to the lithium salt is 0.01 to 0.1:1.

[0020] According to some embodiments of the present invention, the total mass of the molten salt and the lithium salt accounts for 1% to 50% of the mass of the electrolyte composition, specifically 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or any value therebetween.

[0021] According to some embodiments of the present invention, the mesh fiber material is a nonwoven fabric, i.e., a non-woven fabric. The specific material can be selected from conventional types in the art, and non-limiting examples include: PP, PE, PET, PAN or PTFE, or a combination of at least two thereof.

[0022] According to some embodiments of the present invention, the mesh fiber material satisfies at least one of the following A to C: A: thickness is 1 to 100 μm; B: porosity is 30% to 80%; C: average pore size is 0.5 to 20 μm.

[0023] Specifically, the thickness may be 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, or any value therebetween. The porosity may be 30%, 40%, 50%, 60%, 70%, 80%, or any value therebetween. The average pore size may be 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 15 μm, 20 μm, or any value therebetween.

[0024] Controlling the thickness, porosity or pore size within the above range is more conducive to ensuring strength. In addition, appropriate porosity or mesh size can better accommodate other components such as solid electrolytes, lithium salts, molten salts, etc., which is beneficial to improving the ionic conductivity of the composite solid electrolyte membrane.

[0025] According to some embodiments of the present invention, the solid electrolyte includes at least one of a sulfide solid electrolyte, a halide solid electrolyte, and an oxide solid electrolyte. Among them, the sulfide solid electrolyte has a more excellent ion conductivity, and the halide and oxide solid electrolytes have better stability and are less prone to side reactions. Since the chemical stability of molten salts is high, the use of sulfide solid electrolytes can also ensure stability.

[0026] Specifically, non-limiting examples of sulfide solid electrolytes include: containing, for example, Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, In) and S element, and in addition, may contain halogen elements (at least one of Cl, Br, I) or O element. The sulfide solid electrolyte may be glass-type, glass-ceramic type, or crystalline. Crystalline types, such as Thio-LISICON type crystalline phase, LGPS type crystalline phase, silver-germanite type crystalline phase, etc. In addition, as oxide solid electrolytes and halide solid electrolytes, well-known solid electrolytes can be used. For example, an oxide solid electrolyte contains at least Li and O elements, non-limiting examples: garnet type, perovskite type, etc.; a halide solid electrolyte contains at least Li and halogen elements, non-limiting examples: Li 3 InCl 6 , Li 2 CdCl 4 , Li 2 MgCl 4 , Li 2 ZnI 4 , Li 2 CdI 4 The solid electrolyte can be purchased from the market or prepared by methods known in the art.

[0027] According to some embodiments of the present invention, the composite solid electrolyte membrane also includes a binder for promoting adhesion between components. The present invention does not specifically limit the type and amount of the binder. The binder can be of a type known in the art, and non-limiting examples include: polyvinylidene fluoride, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, polytetrafluoroethylene, cellulose (e.g., carboxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, methyl hydroxyethyl cellulose, hydroxypropyl cellulose), polyvinyl acetate, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene butadiene rubber, fluororubber, styrene / ethylene / butene copolymer (SEBS), hydrogenated SBS, polyamide, polyimide, polyacrylamide and acrylic polymer (e.g., sodium polyacrylate) at least one. The amount of the binder can be determined according to specific needs and experience, for example, it can be selected as 0.1% to 10% of the mass of the electrolyte composition.

[0028] According to some embodiments of the present invention, the mass of the binder accounts for 0.1% to 5% of the mass of the electrolyte composition.

[0029] According to some embodiments of the present invention, the electrolyte composition is simultaneously attached to the mesh of the mesh fiber material and to at least one side surface thereof. Wherein, when the electrolyte composition is attached to both sides of the mesh fiber material, the types of solid electrolytes located on the two sides of the surface may be the same or different. For example, a sulfide solid electrolyte may be used on the side where the solid electrolyte membrane contacts the positive electrode sheet to ensure conductivity; a halide solid electrolyte may be used on the side where the solid electrolyte membrane contacts the negative electrode sheet to reduce side reactions and improve battery stability.

[0030] According to some embodiments of the present invention, the thickness of the composite solid electrolyte membrane is 15 to 100 μm, for example, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm or any value between any two. Due to the use of non-woven fabrics, the mechanical properties of the solid electrolyte membrane are improved, and the membrane thickness can be appropriately reduced under the premise of meeting the use requirements. The reduction in membrane thickness not only reduces the cost of raw materials, but also reduces the volume of the electrolyte, which is conducive to improving energy density and reducing battery production costs.

[0031] The second embodiment of the present invention relates to a method for preparing the above-mentioned composite solid electrolyte membrane, comprising: mixing the electrolyte composition with a solvent to prepare a slurry, applying the obtained slurry to at least one side surface of the mesh fiber material, and drying to obtain the composite solid electrolyte membrane.

[0032] The method for preparing a composite solid electrolyte membrane according to the second aspect of the present invention has at least the following beneficial effects:

[0033] During the slurrying process, the solvent can dissolve the lithium salt and the molten salt (and also the binder when the binder is included) to achieve uniform mixing. The solid electrolyte is difficult to dissolve, so a slurry is formed with the solid electrolyte as the dispersed phase and the solution containing the lithium salt and the molten salt as the continuous phase. The lithium salt and the molten salt can wrap around the solid electrolyte particles, fill in the internal gaps of the solid electrolyte after drying, and coat the surface of the solid electrolyte, effectively improving the ion conduction characteristics and mechanical properties of the solid electrolyte membrane.

[0034] The solid electrolyte slurry is coated on the surface of the mesh fiber material. After drying, the solid content in the slurry is filled in the pores of the non-woven fabric, and the mechanical properties of the electrolyte membrane are improved with the non-woven fabric as support. In addition, since pulping can promote the uniform dispersion of the solid content (except the solvent) in the slurry, on this basis, the porous structure of the non-woven fabric is used as a template, and the above-mentioned solid components are evenly distributed in the mesh fiber material to construct a wide conductive network, effectively ensuring the ion conduction performance.

[0035] According to some embodiments of the present invention, the solvent is selected from at least one of alcohols, ethers, esters, ketones, nitriles, amides, sulfones, and sulfoxides. The present invention has no particular limitation on the specific type of solvent, which may be a single solvent or a mixture of two or more solvents.

[0036] Among them, non-limiting examples of alcohol solvents include: methanol, ethanol, n-propanol, isopropanol, butanol, benzyl alcohol, propylene glycol, butanediol, triethylene glycol, hexylene glycol, ethoxylated diethylene glycol or dipropylene glycol.

[0037] Non-limiting examples of ether solvents include: ethyl ether, dimethyl ether, diethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, dioxolane, dioxane, 4-methyldioxolane or anisole. It should be noted that alcohol ether solvents (such as methyl glycol ether, ethyl glycol ether or isopropyl glycol ether) can also be classified as alcohol or ether solvents.

[0038] Non-limiting examples of ester solvents include triglycerides, ethyl acetate, butyl acetate, isobutyl isobutyrate, γ-butyrolactone, diethylene glycol ether acetate, or methoxypropyl acetate.

[0039] Non-limiting examples of ketone solvents include: acetone, methyl ethyl ketone, or methyl isobutyl ketone.

[0040] Non-limiting examples of nitrile solvents include acetonitrile, propionitrile, butyronitrile, succinonitrile or benzonitrile.

[0041] Non-limiting examples of amide solvents include: N,N-dimethylformamide, N,N-dimethylacetamide, fatty acid amides or N-alkylpyrrolidone.

[0042] Non-limiting examples of sulfone or sulfoxide solvents include sulfolane or dimethyl sulfoxide.

[0043] Any one of the above solvents can be selected according to specific needs, or a combination of any two or more solvents can be selected. In addition, other solvents known in the art that can dissolve lithium salts and molten salts can also be used.

[0044] According to some embodiments of the present invention, the solid content of the slurry is 35% to 60%, for example, specifically 35%, 40%, 45%, 50%, 55%, 60% or any value therebetween. The solid content of the slurry is the mass fraction of other components (such as the electrolyte composition) except the solvent. The present invention has no strict restrictions on the solid content of the slurry, and can be adjusted according to actual needs and experience.

[0045] According to some embodiments of the present invention, the electrolyte composition is mixed with a solvent to prepare pulp, and the specific method is: all components of the electrolyte composition (including solid electrolyte, lithium salt and molten salt, and further including a binder) are mixed with a solvent to prepare pulp in one step; or the lithium salt and the molten salt are first compounded, and then mixed with the remaining components and the solvent to prepare pulp. Since lithium salt and molten salt have good solubility, are easy to dissolve and evenly disperse, the one-step pulping method can simplify the process and improve production efficiency.

[0046] According to some embodiments of the present invention, the coating is performed by blade coating or casting process.

[0047] According to some embodiments of the present invention, the drying temperature is 40-80° C. For example, it can be 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C. or any value therebetween.

[0048] According to some embodiments of the present invention, the drying time is 2 to 24 hours. For example, it can be 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours or any value therebetween.

[0049] By controlling the drying temperature and time, the side reactions can be reduced while ensuring the drying rate.

[0050] According to some embodiments of the present invention, the slurrying includes stirring or grinding. There is no specific requirement for the process parameters such as the stirring or grinding speed. As an example, the stirring or grinding speed can be selected as 300 to 10000 rpm, and the processing time can be selected as 1 to 10 minutes. When the solid electrolyte needs to be refined, a grinding process can be selected for slurrying.

[0051] According to some embodiments of the present invention, the slurrying and / or drying is performed at an ambient dew point temperature of less than -50°C (standard atmospheric pressure), thereby reducing the impact of ambient moisture and improving the long-term stability of the solid electrolyte.

[0052] According to some embodiments of the present invention, the slurrying and / or drying is performed under an inert atmosphere (eg, nitrogen).

[0053] A third aspect of the present invention provides a solid-state battery, comprising a positive electrode sheet, a negative electrode sheet and the above-mentioned composite solid electrolyte membrane.

[0054] Solid-state batteries use the above-mentioned composite solid electrolyte membrane, which can effectively reduce the interface internal resistance by virtue of the advantages of the solid electrolyte membrane in mechanical strength and ionic conductivity, so that the battery can maintain higher stability and longer service life during the charging and discharging process, and improve the safety of use. The battery can be prepared by conventional methods and is suitable for large-scale industrial production.

[0055] A fourth aspect of the present invention provides an electrical device comprising the above-mentioned solid-state battery.

[0056] The electrical device adopts the above solid-state battery, which significantly improves the safety and service life of the electrical device due to its advantages in mechanical strength, ion conductivity and stability. By enhancing the structural strength and ion conduction efficiency of the battery, it can better cope with high-load working environments, extend the battery life, improve its stability under long-term operating conditions, and improve endurance.

[0057] According to some embodiments of the present invention, the power-consuming device includes electric vehicles (such as hybrid electric vehicles, pure electric vehicles, extended-range electric vehicles, electric engineering vehicles, electric motorcycles, electric bicycles, etc.), energy storage devices (such as household energy storage systems, photovoltaic energy storage systems), mobile devices (such as smart phones, tablet computers, laptops, etc.), etc. Using the solid-state battery as a power source can provide more durable and efficient energy output, which not only extends the cruising range of the device, but also improves the safety of long-term use.

[0058] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0059] Embodiments of the present invention are described in detail below. The embodiments are exemplary and are only used to explain the present invention, but should not be construed as limiting the present invention.

[0060] In the following examples and comparative examples, some raw materials are described as follows:

[0061] Sulfide solid electrolyte: Li 6 PS 5 Cl(LPSC).

[0062] Halide solid electrolyte: Li 3 InCl 6 (lithium indium chloride, LIC).

[0063] Non-woven fabric: PET, thickness 15 μm, average pore size 5 μm, porosity 80%.

[0064] Unless otherwise specified, all raw materials and equipment used are commercially available conventional products.

[0065] Example 1

[0066] This embodiment prepares a solid electrolyte membrane, including the following preparation steps:

[0067] S1: Weigh the sulfide solid electrolyte, TBA-TFSA, Li-TFSA and SEBS binder, wherein the mass ratio of TBA-TFSA to Li-TFSA is 0.05:1, the total mass fraction of TBA-TFSA and Li-TFSA is 1%, and the mass fraction of SEBS binder is 2%. Put the above raw materials into isobutyl isobutyrate solvent, stir and mix with a stirrer, control the ambient dew point temperature to be less than -50°C (under standard atmospheric pressure), and stir at a constant speed of 1400rpm for 1 minute to obtain a slurry (solid content 40%).

[0068] S2: The slurry is evenly coated on the upper and lower surfaces of the non-woven fabric, and dried in an oven at 60°C for 24 hours. During the drying process, the dew point temperature of the environment is kept below -50°C, or nitrogen is filled into the environment for protection to obtain a composite solid electrolyte membrane with a dry film thickness of 30 μm.

[0069] Example 2

[0070] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 4%, and the other preparation methods and conditions are the same as those in embodiment 1.

[0071] Example 3

[0072] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 6%, and the other preparation methods and conditions are the same as those in embodiment 1.

[0073] Example 4

[0074] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 8%, and the other preparation methods and conditions are the same as those in embodiment 1.

[0075] Example 5

[0076] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 10%, and the other preparation methods and conditions are the same as those in embodiment 1.

[0077] Example 6

[0078] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 20%, and the other preparation methods and conditions are the same as those in embodiment 1.

[0079] Example 7

[0080] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 30%, and the other preparation methods and conditions are the same as those in embodiment 1.

[0081] Example 8

[0082] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 40%, and the other preparation methods and conditions are the same as those in embodiment 1.

[0083] Example 9

[0084] The difference between this embodiment and embodiment 1 is that the total mass fraction of TBA-TFSA and Li-TFSA is 50%, and the other preparation methods and conditions are the same as those in embodiment 1.

[0085] Example 10

[0086] S1: Weigh the halide solid electrolyte, TBA-TFSA, Li-TFSA and SEBS binder, wherein the mass ratio of TBA-TFSA to Li-TFSA is 0.05:1, the total mass fraction of TBA-TFSA and Li-TFSA is 1%, and the mass fraction of SEBS binder is 2%. Put the above raw materials into isobutyl isobutyrate solvent, stir and mix with a stirrer, control the ambient dew point temperature to be less than -50°C (under standard atmospheric pressure), and stir at a constant speed of 1400rpm for 1 minute to obtain a slurry (solid content 40%).

[0087] S2: The slurry is evenly coated on the upper and lower surfaces of the non-woven fabric, and dried in an oven at 60°C for 24 hours. During the drying process, the dew point temperature of the environment is kept below -50°C, or nitrogen is filled into the environment for protection to obtain a composite solid electrolyte membrane with a dry film thickness of 30 μm.

[0088] Embodiment 11

[0089] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 4%, and the other preparation methods and conditions are the same as those of embodiment 10.

[0090] Example 12

[0091] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 6%, and the other preparation methods and conditions are the same as those of embodiment 10.

[0092] Example 13

[0093] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 8%, and the other preparation methods and conditions are the same as those of embodiment 10.

[0094] Embodiment 14

[0095] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 10%, and the other preparation methods and conditions are the same as those of embodiment 10.

[0096] Embodiment 15

[0097] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 20%, and the other preparation methods and conditions are the same as those of embodiment 10.

[0098] Example 16

[0099] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 30%, and the other preparation methods and conditions are the same as those of embodiment 10.

[0100] Embodiment 17

[0101] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 40%, and the other preparation methods and conditions are the same as those of embodiment 10.

[0102] Embodiment 18

[0103] The difference between this embodiment and embodiment 10 is that the total mass fraction of TBA-TFSA and Li-TFSA is 50%, and the other preparation methods and conditions are the same as those of embodiment 10.

[0104] Comparative Example 1

[0105] S1: Weigh the sulfide solid electrolyte and SEBS binder, wherein the mass fraction of SEBS binder is 2%. Put the above raw materials into isobutyl isobutyrate solvent, stir and mix with a stirrer, control the ambient dew point temperature to be less than -50°C (under standard atmospheric pressure), and stir at a constant speed of 1400 rpm for 1 minute to obtain a slurry (solid content 40%).

[0106] S2: Coat the above slurry on an aluminum foil current collector and dry it in an oven at 60°C for 24 hours. During the drying process, keep the dew point temperature of the environment below -50°C, or fill the environment with nitrogen for protection. Peel off the aluminum foil to obtain a composite solid electrolyte membrane with a dry film thickness of 30 μm.

[0107] Comparative Example 2

[0108] S1: Weigh the halide solid electrolyte and SEBS binder, wherein the mass fraction of SEBS binder is 2%. Put the above raw materials into isobutyl isobutyrate solvent, stir and mix with a stirrer, control the ambient dew point temperature to be less than -50°C (under standard atmospheric pressure), and stir at a constant speed of 1400 rpm for 1 minute to obtain a slurry (solid content 40%).

[0109] S2: Coat the above slurry on an aluminum foil current collector and dry it in an oven at 60°C for 24 hours. During the drying process, keep the dew point temperature of the environment below -50°C, or fill the environment with nitrogen for protection. Peel off the aluminum foil to obtain a composite solid electrolyte membrane with a dry film thickness of 30 μm.

[0110] Comparative Example 3

[0111] The difference between this comparative example and Example 1 is that the mass ratio of TBA-TFSA to Li-TFSA is 1:0.5, and the other preparation methods and conditions are the same as those in Example 1.

[0112] Comparative Example 4

[0113] The difference between this comparative example and Example 1 is that the mass of Li-TFSA is 0, the mass fraction of TBA-TFSA is 1%, and the other preparation methods and conditions are the same as those in Example 1.

[0114] Comparative Example 5

[0115] The difference between this comparative example and Example 1 is that the molten salt is 1-butyl-3-methylimidazole bis(trifluorosulfonyl)imide (CAS No.: 174899-83-3), the mass ratio of the molten salt to Li-TFSA is 0.05:1, and the other preparation methods and conditions are the same as those in Example 1.

[0116] Comparative Example 6

[0117] The difference between this comparative example and Example 1 is that step S2 is different, and the other preparation methods and conditions are the same as those of Example 1.

[0118] S2: Coat the slurry obtained in step S1 on an aluminum foil current collector, and dry it in an oven at 60°C for 24 hours. During the drying process, keep the dew point temperature of the environment less than -50°C, or fill the environment with nitrogen for protection. Peel off the aluminum foil to obtain a composite solid electrolyte membrane with a dry film thickness of 30 μm.

[0119] Test Case

[0120] The ionic conductivity, crack resistance and mechanical properties of the composite solid electrolyte membranes prepared in the above embodiments and comparative examples were tested. The test results are shown in Table 1.

[0121] Among them, the ionic conductivity is tested by an AC impedance tester, and the specific test conditions are: temperature: 25°C, frequency: 0.01~7MHz.

[0122] Anti-cracking performance: Wrap the composite solid electrolyte membrane around a cylinder with a diameter of 1 cm and visually inspect whether cracks occur.

[0123] Mechanical properties: The tensile machine was used to test and the maximum force (i.e., tensile force) at which the specimen was pulled apart was recorded. The dimensions of the specimen were: 10 cm long, 1 cm wide, and 30 μm thick, and the tensile rate was set to 5 mm / min.

[0124] Table 1

[0125]

[0126]

[0127] From the above results, it can be seen that the embodiment adopts a combination of solid electrolyte, TBA-TFSA, lithium salt and non-woven fabric, which significantly improves the ionic conductivity, crack resistance and mechanical properties of the solid electrolyte membrane.

[0128] Compared with Example 1, and compared with Example 10, Comparative Example 2 has no addition of TBA-TFSA and lithium salt, resulting in significantly lower ionic conductivity of Comparative Example 1 and Comparative Example 2 than Example 1 and Example 10, respectively. In addition, both Comparative Example 1 and Comparative Example 2 have cracking phenomena, and the mechanical properties are significantly reduced, which may be related to the following factors: (1) lack of support from non-woven fabrics; (2) lack of cushioning effect provided by the low modulus of TBA-TFSA.

[0129] In Comparative Example 3, the proportion of TBA-TFSA is too high, resulting in a decrease in ionic conductivity; in Comparative Example 4, all lithium salts are replaced with TBA-TFSA, and the ionic conductivity is further reduced. This shows that in order to obtain excellent ionic conductivity, it is necessary to reasonably control the content of TBA-TFSA.

[0130] In Comparative Example 5, other molten salts were used instead of TBA-TFSA, resulting in an ionic conductivity lower than that of Example 1. This may be because TBA-TFSA has better compatibility with other components and can significantly improve the interfacial conductivity.

[0131] In Comparative Example 6, no non-woven fabric was used, resulting in a significant decrease in tension. It shows that non-woven fabrics can significantly improve mechanical strength. Based on this advantage, not only can the processability of solid-state batteries be improved (the electrolyte membrane is not easy to break during processing), but also the cycle performance can be guaranteed at a lower electrode coating amount. It should be noted that due to the presence of non-woven fabrics, it is conducive to building a wide range of ion conduction networks, so the addition of non-woven fabrics will basically not have a negative impact on the conductivity of the electrolyte membrane, thereby significantly improving the mechanical properties while ensuring ionic conductivity.

[0132] It can be understood that since the ionic conductivity, crack resistance and mechanical properties of the solid electrolyte membrane are significantly improved, the cycle capacity and cycle stability of the battery can be improved, which helps to improve the cruising range and long-term safety of electrical devices such as electric vehicles.

[0133] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A composite solid electrolyte membrane, characterized in that: Contains the following ingredients: Mesh fiber materials; An electrolyte composition, wherein the electrolyte composition is entirely attached to the mesh holes of the mesh fiber material, or is simultaneously attached to the mesh holes and at least one side surface of the mesh fiber material; the electrolyte composition comprises a solid electrolyte, a lithium salt and a molten salt, wherein the molten salt is selected from tetrabutylammonium bistrifluoromethanesulfonate, and the mass ratio of the molten salt to the lithium salt is less than or equal to 1:

1.

2. The composite solid electrolyte membrane according to claim 1, characterized in that: The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), and lithium oxalate; and / or, the mass ratio of the molten salt to the lithium salt is 0.01 to 0.1:1; and / or, the total mass of the molten salt and the lithium salt accounts for 1% to 50% of the mass of the electrolyte composition.

3. The composite solid electrolyte membrane according to claim 1, characterized in that: The mesh fiber material is a nonwoven fabric; and / or the electrolyte composition is simultaneously attached to the mesh holes of the mesh fiber material and to at least one side surface thereof.

4. The composite solid electrolyte membrane according to claim 1 or 3, characterized in that: The mesh fiber material satisfies at least one of the following A to C: A: thickness is 1 to 100 μm; B: Porosity is 30% to 80%; C: The average pore size is 0.5 to 20 μm.

5. The composite solid electrolyte membrane according to claim 1, characterized in that: The electrolyte composition further includes a binder; Optionally, the mass of the binder accounts for 0.1% to 10% of the mass of the electrolyte composition.

6. The composite solid electrolyte membrane according to claim 1, characterized in that: The solid electrolyte includes at least one of a sulfide solid electrolyte, a halide solid electrolyte, and an oxide solid electrolyte; and / or the thickness of the composite solid electrolyte membrane is 15 to 100 μm.

7. The method for preparing a composite solid electrolyte membrane according to any one of claims 1 to 6, characterized in that: include: The electrolyte composition is mixed with a solvent to prepare a slurry, and the obtained slurry is coated on at least one side of the surface of the mesh fiber material, and dried to obtain the composite solid electrolyte membrane.

8. The preparation method according to claim 7, characterized in that: The solvent is selected from at least one of alcohols, ethers, esters, ketones, nitriles, amides, sulfones and sulfoxides; and / or the solid content of the slurry is 35% to 60%; and / or the drying temperature is 40 to 80° C.; and / or the drying time is 2 to 24 hours.

9. A solid-state battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, and a composite solid electrolyte membrane as described in any one of claims 1 to 6.

10. An electrical device, characterized in that: Comprising a solid-state battery as described in claim 9.